2022
DOI: 10.1111/pce.14442
|View full text |Cite
|
Sign up to set email alerts
|

Drought and low temperature‐induced NF‐YA1 activates FT expression to promote citrus flowering

Abstract: Flower induction in adult citrus is mainly regulated by drought and low temperatures. However, the mechanism of FLOWERING LOCUS T regulation of citrus flowering (CiFT) under two flower‐inductive stimuli remains largely unclear. In this study, a citrus transcription factor, nuclear factor YA (CiNF‐YA1), was found to specifically bind to the CiFT promoter by forming a complex with CiNF‐YB2 and CiNF‐YC2 to activate CiFT expression. CiNF‐YA1 was induced in juvenile citrus by low temperature and drought treatments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Among these, OsGhd8 (OsNF-YB11) delays flowering under long-day (LD) conditions but promotes flowering under short-day (SD) conditions by regulating OsEhd1, OsRFT1, and OsHd3a expression [25]. It was recently found that CiNF-YA1 could specifically bind to the CiFT promoter by forming a complex with CiNF-YB2 and CiNF-YC2 to promote flowering of adult lemon (Citrus limon) under drought and low temperatures [26]. In woody plants, RhNF-YC9 can be inhibited by ethylene to regulate petal expansion in rose (Rosa hybrida) [27].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, OsGhd8 (OsNF-YB11) delays flowering under long-day (LD) conditions but promotes flowering under short-day (SD) conditions by regulating OsEhd1, OsRFT1, and OsHd3a expression [25]. It was recently found that CiNF-YA1 could specifically bind to the CiFT promoter by forming a complex with CiNF-YB2 and CiNF-YC2 to promote flowering of adult lemon (Citrus limon) under drought and low temperatures [26]. In woody plants, RhNF-YC9 can be inhibited by ethylene to regulate petal expansion in rose (Rosa hybrida) [27].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, NF‐YA1 is involved in multiple biological processes, including nodule differentiation (Hossain et al., 2016), rhizobial infection (Laporte et al., 2014), nitrogen‐fixing nodule symbioses (Bu et al., 2020), flowering (Zhou et al., 2022), seed germination (Siriwardana et al., 2014), and abiotic stresses (Ma, Li, & Wang, 2015; Ma, Zhu, et al., 2015). Thus far, NF‐YA1 has not been reported to regulate the development of storage roots in sweet potato.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, drought-induced flowering in citrus was also accompanied by the upregulation of the CiFT expression level [37,90]. Earlier studies have also shown that Citrus latifolia flowering is also induced by drought stress, and that all citrus plant species share this same flowering mechanism [91,92]. Additionally, the perennial woody plant Sapium sebiferum takes 3-5 years to flower normally, but one-year-old seedlings under drought stress flower early, which provides a feasible way to shorten the vegetative growth years of woody plants in genetic research and breeding efforts [36].…”
Section: Flowering Time Of Various Plant Species In Response To Droug...mentioning
confidence: 94%
“…Also, Arabidopsis ABF3 and ABF4 act with NF-YCs to mediate drought-accelerated flowering by regulating SOC1 [95] (Figure 1). In citrus, CiNF-YA1 was also found to promote drought-induced flowering by forming a complex with CiNF-YB2 and CiNF-YC2 to activate CiFT expression, and overexpression of CiNF-YA1 in citrus increased plants drought-sensitivity [92]. It is evident that NF-YAs are likely to be functionally conserved in regulating flowering in annual and perennial plants, with functional diversity resulting from physiological differences in response to stress.…”
Section: Molecular Regulatory Mechanisms Of Flowering Involved In Dro...mentioning
confidence: 99%
See 1 more Smart Citation